Ties that bind: exploring corporate networks, decision-making dynamics in the financial market, labor-management relations, and organizational performance - Emerson Jorge da Silva; Fernando Maciel Ramos; Priscila Cembranel; Cleonice Witt (Future Business Journal)
Abstract Corporate governance relies significantly on the board of directors, who act as custodians of shareholders' interests. The dynamics of social connections between Chief Executive Officers (CEOs) and board members form a critical element that influences information exchange within this vital governance structure. This study seeks to assess the impact of these social connections on organizational performance. We conducted a comprehensive analysis of the professional backgrounds of CEOs and board members to measure the extent of their social connections. Employing multiple regression analysis with robust error corrections, we considered essential economic and financial metrics, including Return on Assets (ROA), Return on Equity (ROE), and Earnings before Interest, Taxes, Depreciation, and Amortization (EBITDA). Our findings reveal that professional social connections have a positive influence on ROA (β = 0.0230|p-value ≤ 0.05) and EBITDA (β = 420,517,1|p-value ≤ 0.05), while educational connections exhibited no significant effect, and familial connections were found to adversely affect EBITDA (β = − 516,307,0|p-value ≤ 0.05). This study highlights the real influence of social connections on firm performance, shedding light on the complex interplay between social dynamics and corporate success. These insights contribute to a more comprehensive understanding of corporate governance and the factors driving organizational performance. Graphical abstract